The prevalence of suicidal thoughts and behaviours among college students: a meta-analysis. - Mortier, P.; Cuijpers, P.; Kiekens, G.; Auerbach, R. P.; Demyttenaere, K.; Green, J. G.; Kessler, R. C.; Nock, M. K.; Bruffaerts, R. (Psychological Medicine, 2018)
Background: Adolescence and young adulthood carry risk for suicidal thoughts and behaviours (STB). An increasing subpopulation of young people consists of college students. STB prevalence estimates among college students vary widely, precluding a validated point of reference. In addition, little is known on predictors for between-study heterogeneity in STB prevalence. Methods: A systematic literature search identified 36 college student samples that were assessed for STB outcomes, representing a total of 634 662 students [median sample size = 2082 (IQR 353-5200); median response rate = 74% (IQR 37-89%)]. We used random-effects meta-analyses to obtain pooled STB prevalence estimates, and multivariate metaregression models to identify predictors of between-study heterogeneity. Results: Pooled prevalence estimates of lifetime suicidal ideation, plans, and attempts were 22.3% [95% confidence interval (CI) 19.5-25.3%], 6.1% (95% CI 4.8-7.7%), and 3.2% (95% CI 2.2-4.5%), respectively. For 12-month prevalence, this was 10.6% (95% CI 9.1-12.3%), 3.0% (95% CI 2.1-4.0%), and 1.2% (95% CI 0.8-1.6%), respectively. Measures of heterogeneity were high for all outcomes (I2 = 93.2-99.9%), indicating substantial between-study heterogeneity not due to sampling error. Pooled estimates were generally higher for females, as compared with males (risk ratios in the range 1.12-1.67). Higher STB estimates were also found in samples with lower response rates, when using broad definitions of suicidality, and in samples from Asia. Conclusions: Based on the currently available evidence, STB seem to be common among college students. Future studies should: (1) incorporate refusal conversion strategies to obtain adequate response rates, and (2) use more fine-grained measures to assess suicidal ideation.